Musculoskeletal Ultrasonography in Detecting Disease Activity in Patients of Juvenile Idiopathic Arthritis: A Cross-Sectional Study - Sharad Dev; Ashish Verma; Anup Singh (Indian Journal of Rheumatology)
Background: Musculoskeletal ultrasonography (MSUS) is a powerful tool to detect subclinical disease in juvenile idiopathic arthritis (JIA). The study was done to compare the results of clinical examination and ultrasonography (US) in identifying disease activity in joints of patients of JIA. Methods: Patients of JIA attending rheumatology clinic of a tertiary care referral center in northern India over a span of 1 year from June 2015 to June 2016 were enrolled in the study. The diagnosis of JIA was established using International League of Associations for Rheumatology 2001 criteria. Clinically determination of synovitis was compared to MSUS parameters of active disease such as synovial hypertrophy, effusion, and increased vascularity in large joints only (bilateral knee, ankle, wrist, and elbow). Results: A total of 108 patients were enrolled in a study period and 864 joints were examined. Synovitis was detected in 305 joints by clinical examination. However, US demonstrated synovitis in 502 joints (additional 209 joints). Twenty patients who were initially thought to be oligoarticular by clinical examination were later classified to polyarticular subtype on the basis of MSUS findings. A significant correlation between erosions and rheumatoid factor and anti-cyclic citrullinated peptide values was found. Conclusion: Our study found that MSUS has a definite role in assessing the disease activity in JIA patients and this modality may be considered as an adjunct in this context, as well as considered for future inclusion in classification criteria for JIA.